2017
DOI: 10.1007/s00792-017-0981-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel trifunctional, family GH10 enzyme from Acidothermus cellulolyticus 11B, exhibiting endo-xylanase, arabinofuranosidase and acetyl xylan esterase activities

Abstract: A novel, family GH10 enzyme, Xyn10B from Acidothermus cellulolyticus 11B was cloned and expressed in Escherichia coli. This enzyme was purified to homogeneity by binding to regenerated amorphous cellulose. It had higher binding on Avicel as compared to insoluble xylan due to the presence of cellulose-binding domains, CBM3 and CBM2. This enzyme was optimally active at 70 °C and pH 6.0. It was stable up to 70 °C while the CD spectroscopy analysis showed thermal unfolding at 80 °C. Xyn10B was found to be a trifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Nonculturable DA111 was found in industrial soft coal slag originating from alum leaching [47]. Culturable Acidothermus promotes the activities of many enzymes, such as endo‐xylanase, arabinofuranosidase, and acetylxylan esterase activities in Acidothermus cellulolyticus 11B [48], and secretes glycoside hydrolases and carbohydrate esterases [49]. These hydrolytic enzymes break down plant cell walls, and the remaining enzymes either degrade components in fungal cell walls or metabolize storage carbohydrates such as glycogen and trehalose [49].…”
Section: Discussionmentioning
confidence: 99%
“…Nonculturable DA111 was found in industrial soft coal slag originating from alum leaching [47]. Culturable Acidothermus promotes the activities of many enzymes, such as endo‐xylanase, arabinofuranosidase, and acetylxylan esterase activities in Acidothermus cellulolyticus 11B [48], and secretes glycoside hydrolases and carbohydrate esterases [49]. These hydrolytic enzymes break down plant cell walls, and the remaining enzymes either degrade components in fungal cell walls or metabolize storage carbohydrates such as glycogen and trehalose [49].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the main oligosaccharide products of oat xylan treated by endo-xylanase alone were identified as xylobiose and Xylo-pentose, and the content of xylo-tetrasaccharide was low ( 50 , 51 ). Xylobiose and pentose are the main products released by endo-xylanase alone ( 52 ). The authors found that α-L arabinofuranosidase was also able to release arabinose and xylose from oat xylan ( 53 ).…”
Section: Enzymatic Hydrolysis For the Production Of Xylo-oligosaccharidementioning
confidence: 99%
“…Acidothermus cellulolyticus 11B, isolated from a hot spring in Yellowstone National Park, produces a tri-functional enzyme that can break down birchwood xylan with high efficiency; in fact, this enzyme has endo-xylanase, arabinofuranosidase, and acetyl-xylan esterase activities [ 141 ].…”
Section: Lignocellulosic Biomassesmentioning
confidence: 99%